Association of serum uromodulin with death, cardiovascular events, and kidney failure in CKD - Steubl, Dominik; Schneider, Markus P.; Meiselbach, Heike; Nadal, Jennifer; Schmid, Matthias C.; Saritas, Turgay; Krane, Vera; Sommerer, Claudia; Baid-Agrawal, Seema; Voelkl, Jakob; Kotsis, Fruzsina; Köttgen, Anna; et al. (Clinical journal of the American Society of Nephrology, 2020)
Background and objectives Uromodulin is exclusively produced by tubular epithelial cells and released into urine and serum. Higher serum uromodulin has been associated with lower risk for kidney failure in Chinese patients with CKD and with lower risk for mortality in the elderly and in patients undergoing coronary angiography. We hypothesized that lower serum uromodulin is associated with mortality, cardiovascular events, and kidney failure in white patients with CKD. - Design, setting, participants, & measurements We measured serum uromodulin in 5143 participants enrolled in the German CKD (GCKD) study. The associations of baseline serum uromodulin with all-cause mortality, major adverse cardiovascular events (MACE; a composite of cardiovascular mortality, nonfatal myocardial infarction or stroke, or incident peripheral vascular disease), and kidney failure (dialysis or transplantation) were evaluated using multivariable Cox proportional hazard regression analyses in a cohort study design, adjusting for demographics, eGFR, albuminuria, cardiovascular risk factors, and medication. - Results The mean age of participants was 60±12 years, 60% were male. Mean serum uromodulin concentration was 98±60 ng/ml, eGFR was 49±18 ml/min per 1.73 m2, and 78% had eGFR <60 ml/min per 1.73 m2. Participants in lower serum uromodulin quartiles had lower eGFR and higher albuminuria, prevalence of diabetes, hypertension, coronary artery disease, and more frequent history of stroke at baseline. During a follow-up of 4 years, 335 participants died, 417 developed MACE, and 229 developed kidney failure. In multivariable analysis, the highest serum uromodulin quartile was associated with lower hazard for mortality (hazard ratio [HR], 0.57; 95% CI, 0.38 to 0.87), MACE (HR, 0.63; 95% CI, 0.45 to 0.90), and kidney failure (HR, 0.24; 95% CI, 0.10 to 0.55) compared with the lowest quartile. - Conclusions Higher serum uromodulin is independently associated with lower risk for mortality, cardiovascular events, and kidney failure in white patients with CKD. - Clinical Trial registry name and registration number Deutsches Register für Klinische Studien (DRKS; German national database of clinical studies), DRKS00003971.
Gesehen am 06.04.2021